The Terms of "Hikmat-e-Kaleemi" and "Hikmat-e-Firhoani" and a review of the Political and Social Situation of the Islamic World (An Overview) - Hashmi, Talib Hussain; Zaidi, Syed Shiraz Ali (sourcecoder, 2024)
The Publication of Allama Iqbal's Masnawi "Pas Cha Baid Kurd O Aqwam-e-Sharq" was published in 1934.When his message was complete and his philosophy had reached the height of its maturity. In his opening speech, Iqbal he looks like an inquisitive pilgrim of the right path, who is moving towards the goal by taking lessons from observations and experiences in the light of common sense, but in Masnavi, "What should be done to the nations of the East", his position is that of a guide. He is one who is aware of the vicissitudes of the path and wants to benefit others from his experiences. The fourteen topics of Masnawi "Pas Cha Baid Kurd" are of great importance. In Allama Iqbal's Masnawi "Pas Che Baid Kard" the following fourteen topics have been discussed in detail. Especially. "Hikmat-e-Kaleemi" and "Hikmat-e-Firhoani". In these two topics (Good and Evil are discussed), what are the benefits of following the path indicated by Allah? What are the disadvantages of not following the path indicated by Allah? It has been discussed extensively.